2006
DOI: 10.1111/j.1742-6723.2006.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine for rapid sequence induction in patients with head injury in the emergency department

Abstract: In the modern acute management of head-injured patients, ketamine might be a suitable agent for induction of anaesthesia, particularly in those patients with potential cardiovascular instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 67 publications
1
53
0
4
Order By: Relevance
“…19 However, even though a systematic review suggested that ketamine is safe for TBI victims, 39 a formal trial is needed to address this question. 40 Thus, the ideal anesthetic agent for TBI victims remains to be identified. Hohl and colleagues suggested that ''the burden of proof is to show that etomidate is as safe as other anesthetics and a noninferiority study would be needed to accomplish this.''…”
Section: Clinical Significance Of Results and Suggestions For Future mentioning
confidence: 99%
“…19 However, even though a systematic review suggested that ketamine is safe for TBI victims, 39 a formal trial is needed to address this question. 40 Thus, the ideal anesthetic agent for TBI victims remains to be identified. Hohl and colleagues suggested that ''the burden of proof is to show that etomidate is as safe as other anesthetics and a noninferiority study would be needed to accomplish this.''…”
Section: Clinical Significance Of Results and Suggestions For Future mentioning
confidence: 99%
“…As such, ketamine is appropriate for patients with traumatic brain injury. Moreover, given the possible impairment in cerebral auto-regulation in traumatic brain injury, the brain's perfusion pressure becomes critically dependent on mean arterial pressure, rendering a clinical scenario in which ketamine's cardiovascular stability may be beneficial [49] . Ketamine is a useful analgesic drug for use outside the operating room due to its excellent analgesia, which is similar to morphine or fentanyl, but with a lower incidence of respiratory depression, as demonstrated in pain control for patients with fractures, burns, and traumatic amputations [50,51] .…”
Section: Use Outside the Operating Roommentioning
confidence: 99%
“…1 However, the evidence supporting the long-standing notion that ketamine increases ICP is rather limited, 10,11,15,17,18,25,30,32,33,38 and several other studies actually refute it. 5,6,8,22,26,35 Based on anecdotal experience, we hypothesized that ketamine does not increasebut may rather effectively decrease-ICP in patients with intracranial hypertension.…”
mentioning
confidence: 94%